Mechanisms of RNA N6-Methyladenosine in Hepatocellular Carcinoma: From the Perspectives of Etiology - Lu, Jiahua; Qian, Junjie; Yin, Shengyong; Zhou, Lin; Zheng, Shusen; Zhang, Wu (Frontiers in Oncology, 2020)
N6-Methyladenosine (m6A) is the most common RNA internal modification in eukaryotic cells. Its regulatory effects at the post-transcriptional level on both messenger RNAs (mRNAs) and noncoding RNAs have been widely studied; these include alternative splicing, stability, translation efficiency, nucleus export, and degradation. m6A modification is implicated in a series of physiological and pathological activities, such as embryonic stem cell differentiation, immunoregulation, adipogenesis, and cancer development. Recently, the significance of m6A methylation has been identified in both viral hepatitis and non-alcohol fatty liver disease (NAFLD), which are major risk factors in the development of hepatocellular carcinoma (HCC). Given the high incidence and mortality rate of HCC worldwide, it is of great importance to elucidate the mechanisms underlying HCC initiation and progression. m6A as an emerging research focus has great potential to facilitate the understanding of HCC, particularly from an etiological perspective. Thus, in this review, we summarize recent progress in understanding m6A modification related to viral hepatitis, NAFLD, and HCC, including their mechanisms and clinical applications.